Cumplimiento crediticio en las cuentas por cobrar de la Empresa Serviagro Expo-Agrícola SAS., durante los ejercicios fiscales 2020-2021. - Vera Reina, Anabel Mercedes (2022)
Serviagro Expo Agrícola SAS, is a company specialized in the commercialization of agricultural inputs, and this case study is oriented towards the credit process with the aim of improving it. Good management of credit compliance is the key to success in an organization, therefore, it allows us to move to the same level as sales already made, because it would be useless to have the flow of sales, if the goal is not met, which is a fast collection of it; so it is not about maintaining a good profit margin, but about having physical evidence of the money at the right time. From the analysis the question arises "Credit compliance in accounts receivable from SERVIAGRO EXPO-AGRÍCOLA SAS., in the Baba canton during fiscal years 2020-2021»". The general objective of this case study is to analyze credit compliance and determine to what extent a credit default affects the company's accounts receivable and therefore liquidity through its policies applied in the 2020 - 2021 financial year. All credit policies have associated collection periods to monitor compliance with overdue customer loyalty credits, which is achieved through overdue invoices and portfolio reports. These same policies are terms and conditions that should be considered when evaluating potential customers and seeing if they are likely to cancel said product. The establishment of bad credit management in the organization leads to daily loss of cash without specific measures to solve the problem.